The Effect of Board Characteristics on Dividend Policy of the Turkish-Listed Companies : An Agency Perspective - Mirzayev, Jabrayil (ADA University, 2020)
In recent years, corporate governance has been one of the most explored areas in many studies. Particularly, the corporate scandals at the beginning of the 21st century and the new regulations accepted by the authorized organizations in several countries increased the number of studies in this subject. The development of governance standards is a highly important task to reduce agency problems and one of the ways to monitor managers and prevent the possible issues is the possession of good board composition. The board of directors should force managers to pursue corporate objectives. They ought to use different means to protect investors. In our research paper, we have tried to link the board characteristics including board size, female members, independent directors with dividend policy from an agency perspective. We have argued that the mentioned board variables use dividends in order to reduce the agency issues in the corporation. We have analyzed the effect of board characteristics on the dividend policy of the Turkish-listed companies in the period between 2012-2019. The results show that there is a positive and significant relationship between diversity and dividend policy. Moreover, as an interactive term, we have found that despite the fact that a diversified board is much more effective to enforce managers to pay higher dividends, this negatively impacts on firm value in the Turkish-market. Furthermore, we have observed that as the board becomes larger, this positively influences the dividend payments which also positively associated with the corporate value. We did not find any significant effect of outside directors on the payout policy. Our results are robust for all estimations and analysis.
Keywords: Business; Dividends.; Government spending policy -- Turkey.; Government spending policy -- Azerbaijan.; Economic aspects -- Azerbaijan.; Economic aspects -- Turkey.